On Some Indefinite and Non-Powerlike Elliptic Equations - Ubilla-Lopez, P; Ramos-Quoirin, H (2013)
We consider a class of elliptic problems for the operator -?+V, acting on H01(?), where ? is a bounded domain. The main feature here is the indefinite behavior of both the operator and the nonlinearity. Based on the global geometry of the energy functional, we prove the existence of two local minimizers and a mountain-pass critical point for a concave-convex type nonlinearity. Subcritical and critical growth are allowed on the nonlinearity. © 2012 Elsevier Ltd. All rights reserved.